Utilização da PCR para detecção de DNA de Leptospira spp em sêmen e testículo bovino - Ganda, Muriell Ribeiro (2014)
The general objective of this research was to detect the DNA of Leptospira spp. in cattle s semen and testicles by PCR. In order to evaluate the lowest concentration of bacterial DNA that the technique can detect, was held, initially, an experimental infection of semen and testicles. The detection limit obtained was 103 bacteria per ml of semen and 105 leptospires per ml of macerated testicle. In semen samples from 146 bulls from farms and semen s collection, processing and marketing centrals was performed the DNA research. It was not detect the bacteria s genetic material in any sample. However, using the SAM, it were detected agglutinins anti-Leptospira spp. in the serum of 23.97 % of animals with levels ranging between 1/100 and 1/800. Fragments of 32 testicles of cattles slaughtered in a slaughterhouse were analyzed by PCR, and it was not detect Leptospira spp. DNA in any sample. These animals were serologically negative. It was concluded that there is the possibility of the leptospires are not eliminated through semen, or are not being eliminated at the time of sample collection, which could not bring risks of disease s venereal transmission.